Història inèdita de la llengua catalana - Aracil, Lluís V. (Caplletra. Revista Internacional de Filologia, 1996)
In this article, which first appeared in 1983, some thoughts are given to the status of Catalan since the Spanish political transition into democracy. The purpose is to show how present «important» opinionmakers base themselves on an escapist fantasy which replaces real history, which in tur prevents us to study the real past and thus conceive and propose a real future for the language. An analysis is made of the significance of the Renaixença and how this movement considered Catalan as lost. In fact, the ultimate aspirations of regionalists were nowhere near the minimum requirements of a modern European linguistic community. Therefore, the present return to the idyllic recovery practised by the Renaixença is considered even more brutally simplistic and fantastic than what the Renaixença meant. This different analysis of the present situations involves a change in mentality, a different way of thinking. Such mentality must enable us to clarify, not only the wiles coming from outside, but first and foremost, the internal obstacles presented by Catalan society itself.